A DATABASE ON TRANSLATIONAL ENHANCERS TO SUPPORT EXPERIMENTS WITH TRANSGENIC PLANTS - O. G. Smirnova; D. A. Rasskazov; A. V. Kochetov (Вавиловский журнал генетики и селекции)
A database on translational enhancers providing additional control of foreign gene expression at the mRNA translation level has been developed. It contains structured information on the presence of enhancers located within mRNAs, which control gene expression at the posttranscriptional stage. These data can be used to design genetic constructs for plant transgenesis. The database is based on the platform of the Sequence Retrieval System (SRS), allowing users to make a rapid search for enhancers with defined properties and retrieve corresponding nucleotide sequences. The database is available at http://wwwmgs.bionet.nsc.ru/mgs/dbases/trsig/